Estándares para la administración segura de quimioterapia en Pacientes Oncológicos 2015-2020 - Garcia-Saavedra, Liz-Edenia (2021)
Cancer is currently a public health problem. It should be noted that most patients require treatment with chemotherapy and radiotherapy among other procedures to recover their health. The aim of this study was to analyze the development of scientific evidence on standards for the safe administration of chemotherapy in cancer patients. Methodology: a descriptive systematic review was performed with the search of databases in Pub Med and Scopus selected articles from 2015 - 2020 in English and Spanish languages. The results indicate that the safe administration of chemotherapy in oncology patients requires nurses to use updated standardized protocols and care guidelines with continuous training, as well as to carry out preventive actions of monitoring, control and follow-up for compliance with the protocols. It is concluded that adverse events should be socialized among nurses to assume improvement plans and strategies to raise the quality of the services provided by the nursing professional, as well as to avoid errors and complications of malpractice in the administration of chemotherapy.